Renoprotective effects of a dipeptidyl peptidase 4 inhibitor in a mouse model of progressive renal fibrosis. (1st January 2017) - Uchida, Takahiro; Oda, Takashi; Matsubara, Hidehito; Watanabe, Atsushi; Takechi, Hanako; Oshima, Naoki; Sakurai, Yutaka; Kumagai, Hiroo
Abstract: Although the effects of dipeptidyl peptidase 4 (DPP-4) inhibitors beyond their hypoglycemic action have been reported, whether these inhibitors have renoprotective effects in nondiabetic chronic kidney disease (CKD) is unclear. We examined the therapeutic effects of DPP-4 inhibition in mice with unilateral ureteral obstruction (UUO), a nondiabetic model of progressive renal fibrosis. After UUO surgery, mice were administered either the DPP-4 inhibitor alogliptin or a vehicle by oral gavage once a day for 10 days. Physiological parameters, degrees of renal fibrosis and inflammation, and molecules related to renal fibrosis and inflammation were then evaluated using sham-operated mice as controls. Positive area of α-smooth muscle actin was significantly smaller and expression of transforming growth factor β messenger RNA was significantly lower in the alogliptin-treated group than in the vehicle-treated group. Renal total collagen content was also significantly lower in the alogliptin-treated group than in the vehicle-treated group. These results suggest that alogliptin exerted renoprotective antifibrotic effects. The positive area of F4/80 was significantly smaller and expression of CD68 messenger RNA was significantly lower in the alogliptin-treated group than in the vehicle-treated group, suggesting an anti-inflammatory action by the DPP-4 inhibitor. Compared to the results for the vehicle-treated group, expression of markers for M1 macrophages tended to be lower in the alogliptin-treated group, and the relative expression of M2 macrophages tended to be higher. These data indicate the various protective effects of DPP-4 inhibition in nondiabetic mice with UUO. DPP-4 inhibitors may therefore be promising therapeutic choices even for nondiabetic CKD patients.